Comparison between comparative tuberculin and gamma-interferon tests for the diagnosis of bovine tuberculosis in Ethiopia - Ameni, G.; Miorner, H.; Roger, F.; Tibbo, Markos (Springer, 2000)
A study to determine and compare the sensitivities and specificities of the comparative cervical tuberculin (CCT) and gamma-interferon (IFN-gamma) tests for the diagnosis of bovine tuberculosis was conducted on 30 Zebu oxen. The results of the tests were compared with the presence of acid-fast bacilli found by bacteriological culturing and histopathological examinations. The sensitivity and specificity of CCT test were found to be 90.9 percent and 100 percent, respectively. Those of the commercial IFN-gamma test were determined to be 95.5 percent and 87.7 percent, respectively. No significant differences were found between the sensitivities (Yates' corrected X2=0.32; p=0.57) or the specificities (Yates' corrected X2=2.54; p=0.11) of the two tests. Furthermore, a positive correlation (r=0.76) was recorded between the increase in skin thickness following injection of bovine purified protein derivative (PPD) and the optical density in the gamma-interferon assay with bovine PPD. On the other hand, the correlation (r=0.47) between the change in skin thickness following injection of avian PPD and the optical density in the gamma-interferon assay with avian PPD was relatively weak. On the basis of this preliminary investigation, it was concluded that the choice between the two tests depends on their cost and simplicity and on livestock management and time factors rather than on their respective diagnostic value.